Effect of curcumin on aging-related gene expression in fibroblast cells - Nezırı, Sabina (My University, 2021)
The aging process affects almost all species on earth. Intrinsic and extrinsic factors affect aging at different scales. Longitudinal family studies suggest that only 25% of aging is genetic, and the rest is affected by the environment and lifestyle. In recent years food compounds and their influence in the genome and epigenome have gained a lot of attention. Nutraceuticals, or foods with medical benefits are thought to affect lifespan and healthspan. In this research the effect of the well-known compound, curcumin was studied. For centuries, the turmeric plant has been used as a remedy, and curcumin is the most bioactive compound of it. The aim of this thesis is to study the hormetic effect of curcumin, and its effect on senescence and HAS2, IGFBP2, WNT16, GAPDH, ANLN, and CCNB1 gene expressions in late passage foreskin fibroblast. The control group was not treated, while the experimental groups were treated with 1 micromolar curcumin and the other with 0.074% DMSO. All groups were passaged until entering the senescence state. Afterwards, RNA isolation and Real-Time PCR test were done, and the cell viability test was used to find the right curcumin concentration and measure its hormetic effect. As a result, it was found that in our cell line the curcumin retains its hormetic effect. We also show that curcumin affects the expression of CCNB1 and ANLN genes as expected.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Aging; Fibroblast; Curcumin; Gene expression; Senescence